Redox properties of transitional milk from mothers of preterm infants. (9th August 2017) - Minić, Simeon; Ješić, Miloš; Đurović, Dijana; Miletić, Srdjan; Lugonja, Nikoleta; Marinković, Vesna; Nikolić‐Kokić, Aleksandra; Spasić, Snežana; Vrvić, Miroslav M
Abstract : Aim: There is a discrepancy between the amount of transitional milk produced by mothers of preterm infants and the low capacity of premature infants to consume it. This milk can be used in milk banks, but previous studies found that there are large variations in the level of host‐defence proteins in individual samples of milk from mothers of premature infants, which implies that large individual variations in antioxidative defence composition are also possible. Methods: Milk samples were collected from 20 healthy mothers of preterm infants. We determined the values for non‐enzymatic antioxidative capacity parameters (oxygen radical absorbance capacity (ORAC)), static oxidation–reduction potential (ORP), activities of antioxidant defence enzymes and the amount of vitamin C in whole milk, skim and whey fractions of transitional milk. Results: The main low‐molecular‐weight antioxidant in transitional milk is vitamin C and most of it is contained in whey. ORAC is higher in whole transitional milk than in skim milk and whey, and ORP is lower in whole transitional milk than that in skim milk and whey. Antioxidative enzyme activities are similar in all individual samples of transitional milk from mothers of preterm infants. Conclusions: Our results indicate that transitional milk of mothers of preterm infants shows slow individual variations in antioxidative defence composition; therefore, it can be used in human milk banks.